Counselors Practice in Addressing Pornography Issues Among Students in School - Mohd Karim, Dharatun Nissa Fuad; Hamid, Aida Hanim A.; Sajani, Shazlinda; Nordin, Che Fatin Nur Adlina (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to explore the practice of counselors in dealing with pornography issues among students in school. The study employs a case study approach with two experienced counselors handling the issues of pornography among students in schools in Selangor. Data were collected through semi-structured interviews. Then, the data obtained were analyzed manually. Seven themes were developed. The themes were discussed in chronological order, starting from counselors’ understanding and perceptions on the pornography issues to the strategies used to solve the pornography issues within the students’ circle. Overall, as a counselor, the practice in handling the issue of pornography is very important in order to improve the competency of counselors in future similar cases. The findings from this study will serve as a guidance for counselling practitioners to handle issues related to pornography. Given the focus of the study, future studies may consider in developing the interventions and psychoeducation modules for counseling session related to pornography issues.